Współczesne problemy prawa natury a koncepcja świadomości prawnej: [Modern problems of law of nature and concept of sense of law] (Studia Prawnicze / The Legal Studies, 1985)
The author notices the revival of doctrines of law of nature in modern philosophical and legal ideas and mentions three basic questions connected with this trend:1. What are the reasons of the revival and what are the trends in the development of a modern doctrine of law of nature?2. To what degree do trends revert to the classic version of law of nature, and especially “human, nature” and to what degree are they modified when confronted with actual development of knowledge?3. What are the possibilities of a new approach to the problems of law of nature on the basis of a modern concept of legal consciousness which took shape on the basis of the theory of law and sociology of law?Some of the reasons of the revival of doctrines of law of nature are: flexibility of those concepts, experience of fascism and growing interests in the problems of limits of law. At the same time, especially under the influence of discussions on human rights, departure from a classic version of law of nature has been observed in favour of the concept of law of nature with changing content. It arouses, however, a number of reservations of philosophical and methodological nature which also reject modern concepts of law of nature. According to the author, the concept of legal consciousness allows to present the process of forming opinions and postulates on law without resorting to the language of law of nature in theoretical considerations.